PREVENTION OF DENGUE HEMORRHAGIC FEVER (DHF) - Bisra, Marido; Yuliana, Anastasya Shinta (LPPM Universitas Awal Bros, 2024)
Dengue Hemorrhagic Fever (DHF) is still a disease that is feared, especially in tropical countries, including Indonesia. Continuous efforts are needed to prevent dengue fever. In 2012, Indonesia was recorded as the country with the highest number of dengue fever cases in the world based on World Health Organization (WHO) records. One of the factors that spread dengue infection is the Aedes aegypti mosquito. These mosquitoes live and breed in environments that have hot and humid climates such as Indonesia. The aim of this outreach is to provide information to the public about dengue fever, the symptoms of dengue fever and also how to prevent dengue fever. The method used in this counseling is providing material using PowerPoint. The way to prevent dengue fever used in this outreach is to remind the community, especially the community of Bamboo Kuning Pekanbaru sub-district, of knowledge about the causes and consequences that arise from not keeping the environment clean which is at risk of spreading. Dengue Hemorrhagic Fever, increasing insight for the community regarding information about the dangers of dengue fever if quick and appropriate action is not taken, as well as inviting participation and active role from the community, even if possible, becoming ambassadors for the surrounding environment to work together in preventing dengue fever. Dengue Blood. At the same time, you can also get good benefits from this activity by implementing healthy and clean living habits in the surrounding environment, especially where you live.